International trade, factor mobility and the persistence of cultural-institutional diversity - Marianna Belloc; Samuel Bowles (Center for Economic Studies and ifo Institute (CESifo), 2009)
Cultural and institutional differences among nations may result in differences in the ratios of marginal costs of goods in autarchy and thus be the basis of specialization and comparative advantage, as long as these differences are not eliminated by trade. We provide an evolutionary model of endogenous preferences and institutions under autarchy, trade and factor mobility in which multiple asymptotically stable cultural-institutional conventions may exist, among which transitions may occur as a result of decentralized and un-coordinated actions of employers or employees. We show that: i) specialization and trade may arise and enhance welfare even when the countries are identical other than their cultural-institutional equilibria; ii) trade liberalization does not lead to convergence, it reinforces the cultural-institutional differences upon which comparative advantage is based and may thus impede even Pareto-improving cultural-institutional transitions; and iii) by contrast, greater mobility of factors of production favors decentralized transitions to a superior cultural-institutional convention by reducing the minimum number of cultural or institutional innovators necessary to induce a transition.
Keywords: C73; D23; F15; F16; 330; institutions; incomplete contracts; evolutionary game theory; culture; trade integration; factor mobility; globalization; Außenwirtschaft; Internationale Arbeitsteilung; Faktormobilität; Kulturpsychologie; Institutionalismus; Evolutionäre Spieltheorie; Globalisierung; Unvollständiger Vertrag; Theorie